A Study of Different Subsequence Elimination Strategies for the Soft Drink Production Planning - Maldonado, M. [UNESP]; Rangel, S. [UNESP]; Ferreira, D. (Univ Nacional Autonoma Mexico, 2014)
The production of soft drinks involves two main stages: syrup preparation and bottling. To obtain the lots sequence in the bottling stage, three approaches are studied. They are based on the sub-tour elimination constraints used in mathematical models for the Asymmetric Traveling Salesman Problem. Two of the mathematical models are from the literature and use classical constraints. The third model includes multi-commodity flow constraints to eliminate disconnected subsequences. The computational behavior of the three models is studied using instances generated with data from the literature. The numerical results show that there are considerable differences among the three models and indicates that the multi-commodity formulation provides good results but it requires far more computational effort when the instances are solved by a commercial software.
Keywords: Production planning; integrated lot sizing and scheduling models; asymmetric travelling salesman problem; multi-commodity flow